PEMBUATAN SILASE DARI LAMTORO SEBAGAI ALTERNATIF PAKAN PADA MUSIM KEMARAU DI KELOMPOK TANI SAFAHU DI DESA TOLOLAKO KECAMATAN KEMPO KABUPATEN DOMPU - Hasanah, Nur; Amaylia, Annisanur; Arpan Putra, Kurniawan; Putra, M. Nizar Perdana; Satani, Helmi Syahru; Hadijah, Hadijah; Mulisa, Mulisa; Komanik, Ida Jaya; Muzakir, Muzakir; Marselaa, Anis (Jurnal Wicara, 2023)
Silage is a feedstuff processing technique that aims to preserve the feedstuff in fresh form by storing it in an airtight or anaerobic space. This silage making training was carried out in the Safahu farmer group, village. Tololako, Kempo district. dompu, this training aims to provide understanding to the public regarding the preservation of high quality fresh feed ingredients. The method used is by socializing demonstrations and making palkan silage, the socialization process takes 20 days to evaluate. Evaluation of the resulting silage product includes physical observations starting from the texture of the aroma and the level of palatability of livestock. The physical quality of the silage produced is quite good, marked by a slightly sour smell, slightly sour and slightly sweet taste, brownish green color, dry texture and feels soft. following the stages of making silage. This is evidenced by the feedback from the participants who asked questions during the training to find out more about making silage.